Switching Intention Kosmetik Halal Pada Perempuan Muslim Generasi Z : Pendekatan Teori Push-Pull-Mooring - Yasamin, Zahrotul; Susilowati, Fitriah Dwi (Universitas Negeri Surabaya, 2026)
This study analyzes the factors influencing switching intention to use halal cosmetics among Generation Z Muslim women using the Push-Pull-Mooring theory approach. The variables studied include dissatisfaction and regret (push), perceived value and price (pull), and halal awareness and religiosity (mooring). This quantitative study involved 178 Muslim female respondents aged 17–27 who had used cosmetics without a halal label. Data were collected through questionnaires and SEM-PLS analysis using SmartPLS 4. The results showed that dissatisfaction, regret, perceived value, and price significantly influenced switching intention, while halal awareness and religiosity did not. These findings confirm that the intention to switch to halal cosmetics is driven more by dissatisfaction, value and price considerations, and regret from previous purchases than by halal awareness and religiosity.